MEMORY AND NARRATIVE (Andamios, Revista de Investigación Social, 2010)
A large number of novels which refer to the last dictatorship have been published in Argentina recently. These texts turn their eyes toward the past to re-present it, opening new aspects. The senses the novels create, question or expand the imaginary built by the series of policies that commemorates and prioritizes the demand of justice and the ethical rescue of the victims. In this way, the intellectual component of memory that aspires to “understand” can be sometimes pushed away into the background. This article analyzes four novels that shed light on the impact that the experience of the state terrorism and the figure of the “disappeared” had on the ways of narrating and on the conception of identity and time in the present.
Keywords: Memory; dictatorship; narrative; identity; time